2005
DOI: 10.1097/01.sla.0000165198.29398.4b
|View full text |Cite
|
Sign up to set email alerts
|

When Fundoplication Fails

Abstract: Failure of fundoplication is unusual in experienced hands. Most are managed within 2 years of the initial operation. Wrap herniation has now become the most common mechanism of failure requiring redo. Redo fundoplication was successful in 93% of patients, and most could be safely handled laparoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 18 publications
(16 reference statements)
10
104
1
6
Order By: Relevance
“…They found that 34% had symptomatic relapse, and many of them required medical management [15]. Smith and colleagues followed a cohort of 1892 patients for 10 years post fundoplication and found that 17% had resumed using antisecretory medications [16]. Spechler and colleagues followed a cohort of 38 patients for 10 years after fundoplication and found that 62% were using antisecretory medications [17].…”
Section: Myth: Fundoplication Effectively Controls Reflux Symptomsmentioning
confidence: 99%
“…They found that 34% had symptomatic relapse, and many of them required medical management [15]. Smith and colleagues followed a cohort of 1892 patients for 10 years post fundoplication and found that 17% had resumed using antisecretory medications [16]. Spechler and colleagues followed a cohort of 38 patients for 10 years after fundoplication and found that 62% were using antisecretory medications [17].…”
Section: Myth: Fundoplication Effectively Controls Reflux Symptomsmentioning
confidence: 99%
“…[10][11][12] In a series of 307 re-do fundoplications, Smith et al 6 found that fundoplication herniation was the most common mechanism of failure. Symptomatic patients with objective evidence of failure of LARS can be offered re-do surgery: several studies have demonstrated that this can be safely undertaken laparoscopically.…”
Section: Ann R Coll Surg Engl 2010; 92: 131-135 131mentioning
confidence: 99%
“…Failure rates of laparoscopic Nissen fundoplication vary from 2% to 30%, [3][4][5][6][7] depending on the definition of 'failure'. Both patients and clinicians may interpret resumption of medical treatment as failure, but the majority of patients taking antireflux medication are taking it for atypical or non-reflux related symptoms.…”
mentioning
confidence: 99%
“…Patient satisfaction after laparoscopic Nissen fundoplication with 5-year follow-up is 86-96% (Lafullarde et al, 2001;Smith et al, 2005). Complications associated with laparoscopic hiatal hernia surgery include stenosis, pulmonary complications (pneumonia, pneumothorax, pulmonary edema) and gastrointestinal complications (bleeding, perforation, dysphagia).…”
Section: Laparoscopic Repairmentioning
confidence: 99%
“…Complications occur in approximately 15%, slightly increasing with multiple redos. After redo laparoscopic fundoplication 70% of patients is GERD-related symptom free (Smith et al, 2005).…”
Section: Treatment Of Recurrencementioning
confidence: 99%